Mechanical Support as Failure Intervention in Patients with Cavopulmonary Shunts (MFICS): Rationale and Aims of a New Registry of Mechanical Circulatory Support in Single Ventricle Patients. (20th March 2013) - Rossano, Joseph W.; Woods, Ronald K.; Berger, Stuart; Gaynor, J. William; Ghanayem, Nancy; Morales, David L.S.; Ravishankar, Chitra; Mitchell, Michael E.; Shah, Tejas K.; Mahr, Claudius; Tweddell, James S.; Adachi, Iki; et al.
Abstract It is now recognized that a majority of single ventricle patients, those with functionally univentricular hearts, who have survived palliative cavopulmonary connection will experience circulatory failure and end‐organ dysfunction due to intrinsic inadequacies of a circulation supported by a single ventricle. Thus, there are an increasing number of patients with functional single ventricles presenting with failing circulations that may benefit from mechanical circulatory support (MCS). The paucity of experience with MCS in this population, even at high volume cardiac centers, contributes to limited available data to guide MCS device selection and management. Thus, a registry of MCS in this population would be beneficial to the field. A conference was convened in January 2012 of pediatric and adult cardiologists, pediatric cardiac intensivists, congenital heart surgeons, and adult cardiothoracic surgeons to discuss the current state of MCS, ventricular assist device, and total artificial heart therapy for patients who have undergone cavopulmonary connection, either superior cavopulmonary connection or total cavopulmonary connection. Specifically, individual experience and challenges with VAD therapy in this population was reviewed and creation of a multiinstitutional registry of MCS/ventricular assist device in this population was proposed. This document reflects the consensus from the meeting and provides a descriptive overview of the registry referred to as Mechanical Support as Failure Intervention in Patients with Cavopulmonary Shunts.